Reviews (New blackfriars, 1966)
THE BIBLE ON CHRISTIAN UNITY by J. F. Lescrauwaet UNITY IS NOT ENOUGH by M. Gibbard SSJE THE SUPPER AND THE EUCHARIST by J. Wilkinson THE RENEWAL OF WORSHIP Ed. by R. C. D. Jasper ARCHBISHOP ROBERTS by David Abner Hum. Darton, Longman 8 Todd WORSHIP IN A CHANGING CHURCH. Edited by R. S. Wilkinson A SHORT HISTORY OF THE INTERPRETATION OF THE BIBLE by Robert M. Grant THE BOY FROM THE LAKE, by Rosemary Haughton. Darton. Longman and Todd THE SISTINE CHAPEL BEFORE MICHELANGELO: Religious Imagery and Papal Primacy, by L. D. Ettlinger GALILEO: The man, his work, his misfortunes, by James Brodrick, S.J. Geoffrey Chapman